The quest for sustainability : a review of two integrated beach resorts in Southeast Asia. - Gonzales, Gerard Dionicio. (2009)
There has been rapid increase of integrated beach resort (IBR) developments in Southeast Asia in the last two decades. IBR developers and operators are motivated by the potential benefits of synergy, control and critical mass. For governments, IBRs provide valuable foreign exchange and a means to control tourism's negative impacts. Today's holiday-seekers find that IBRs provide an appealing beach vacation lifestyle that differs from the usual run-of-the-mill resorts.